Strategic Human Resource Management: Enhancing Competitive Advantage in Educational Institutions - Agus R, Abu Hasan; Rusdiah, Nadira (MANAZHIM, 2024)
This research aims to understand and analyze competitive advantage through the utilization of human resources to enhance competitiveness at MA Nurul Jadid Paiton Probolinggo. This study is based on the fact that madrasah (Islamic school) becomes the second alternative choice due to the incapacity of human resources or customers' doubts about the teachers' abilities in madrasah. Thus, this research focuses on how strategic human resource management nurtures competitive advantage in a pesantren-based madrasah. To reveal this, the researcher employs a qualitative approach with a case study design. In the process, data is collected through observation, in-depth interviews, and documentation. The data analysis technique used is the Miles and Huberman data analysis technique, which consists of data reduction, data display, and verification. This research generates findings that strategic human resource management in enhancing competitive advantage at MA Nurul Jadid is conducted in the form of; 1) formulation of HR policies and procedures; 2) development and training; 3) integrated performance management, and 4) periodic evaluation and adjustment.